Question

5x − 3(8x − 2)= 10x − 12+ 4(x − 2)

73

likes366 views

Neal

4.5

58 Answers

5x − 3(8x − 2) = 10x − 12+ 4(x − 2)
Distribuir
5x − 24x + 6 = 10x − 12+ 4x − 8
combinar términos semejantes
-19x + 6 = 14x - 20
26 = 33x
Divide ambos lados por 33
x = 26/33

Frequently asked questions (FAQs)

How many grams are in 5 pounds?

+

Math question: "Factorize the expression 4x² + 12xy + 9y² using the distributive property."

+

Question: Factor the expression 3x^2 - 9x + 6 completely using the distributive property.

+

New questions in Mathematics